Peluang Persekongkolan Dengan Anak Perusahaan BUMN Dalam Proses Pengadaan Barang dan Jasa - Samawati, Putu (Universitas Sriwijaya, 2019)
BUMN is a business entity whose entire or part of its capital is owned by the state through direct participation that comes from separate state assets with the main purpose of establishment is to provide benefits to the nation and protect the lives of many people. The number of BUMNs that stand and run businesses in the jurisdiction of Indonesia reaches approximately 121 companies, out of the 121 companies, there are 2 well-known BUMN companies involved in the case and have been decided by KPPU to violate Law No.5 of 1999 concerning Prohibition of Monopolistic Practices and Competition Unhealthy Business. KPPU's decision stating that PT. Pelindo II (Persero) and PT. Pertamina (Persero) involves cases of conspiracy with subsidiaries and / or companies affiliated with SOEs which certainly create an imperfect competition climate and conflict with the objectives of the establishment of BUMN by the state. The problem of conspiracy carried out by SOEs often occurs and is supported by various factors, one of which is supported by interent regulations such as those imposed by the minister of SOEs through BUMN State Ministerial Regulation Number PER-15 / MBU / 2012 concerning Amendments to SOE State Ministerial Regulations Number PER-05 / MBU / 2008 concerning General Guidelines for SOE Goods and Services Procurement, in Article 9 paragraph (3) letter j and Article 9 paragraph (4), which essentially provides opportunities for SOEs to exercise their rights in the procurement of goods and services through direct appointment to subsidiaries and / or BUMN affiliated companies. The enactment of this regulation seems to give privileges to SOEs to be able to conspire with subsidiaries or companies affiliated with BUMN. The thing that became the study of analysis was by looking at the background of the enactment of the ministerial regulation and finding legal efforts to anticipate the occurrence of the conspiracy